(untitled) (Journal of Universal Science Research, 2023)
Taking into account the limited land and water resources and the constant growth of the region’s population, a stable supply of food to the population and exports will be achieved through the rational use of agricultural potential and policy. It is to save water resources that agricultural clusters based on digital technologies are considered one of the main strategic directions.